Rethinking agrifood systems for the post-COVID world - Fan, Shenggen; Chen, Kevin Z.; Si, Wei; Swinnen, Johan (2021)
The outbreak of the COVID-19 pandemic in early 2020 has caused a global public health crisis. It has also severely damaged the world’s agrifood systems. Before the pandemic, agrifood systems were already vulnerable to many threats, including climate change, frequent extreme weather events, degradation of natural resources, economic slowdown, and regional conflicts (Fan, Wei, and Zhang 2020; Chen et al. 2020). The number of undernourished people worldwide had been increasing for five consecutive years to 690 million in 2019. More than 135 million people in 55 countries and territories were facing acute hunger, 144 million children younger than five were stunted, and 47 million children were wasted (FSIN 2020; FAO et al. 2020). The pandemic has increased poverty for the first time in 22 years—about 100 million more people have fallen into extreme poverty (FAO 2021b). Moreover, an additional 130 million people are threatened by acute severe food insecurity during the pandemic (WFP 2020a). A recent study has shown that the total number of children affected by stunting could increase by 2.8 million because of the pandemic (World Bank 2021). At the same time, the number of children experiencing wasting could increase by 6.7 million (UNICEF 2020; WFP 2020b). The livelihoods of vulnerable groups such as smallholder farmers, women, and migrant workers are threatened as they face losing jobs and incomes (FAO 2021b). Without effective measures, 840 million people in the world could face undernourishment and suffer from hunger by 2030, far from the “zero hunger” of the UN Sustainable Development Goals (IFPRI 2021b). As vaccines are gradually deployed globally, the pandemic is expected to be under control to some extent by the end of 2021. But we should not simply recover from the crisis; it is time to rethink how to build back better to achieve green, low-carbon, healthier, inclusive, and more resilient food systems.